Nanopolymer material and method for preparing the same
Patent Information
- Application Number
- CN202610945347.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-10-16
AI Technical Summary
[0009]本发明的目的是提供一种纳米高分子材料及其制备方法,具体而言,本发明所要解决的技术问题包括:(1)纳米无机氧化物颗粒在高分子基体中容易团聚、难以实现纳米尺度均匀分散的问题;(2)现有表面改性方法仅对纳米填料进行单一修饰,界面结合强度不足的问题;(3)现有纳米复合材料难以兼顾优异力学性能、高热稳定性和低介电特性的问题
(1)本发明通过“硅烷偶联剂化学接枝+原位自由基聚合接枝”的多步表面改性策略,在纳米填料表面构筑了具有特定化学组成和链长的高分子刷层。该高分子刷层与高分子基体具有良好的化学相容性,能够通过空间位阻效应有效抑制纳米填料的团聚,使纳米填料在高分子基体中实现真正的纳米尺度均匀分散。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer composite materials technology, and in particular to a nanopolymer material and its preparation method. Background Technology
[0002] With the rapid development of high-tech fields such as electronics, aerospace, and new energy, increasingly higher demands are being placed on the comprehensive performance of polymer materials. Introducing nanoscale inorganic fillers into polymer matrices to prepare nanocomposites has been widely recognized as an effective way to improve the mechanical properties, thermal stability, dielectric properties, and barrier properties of polymer materials. However, achieving uniform dispersion of nanofillers in the polymer matrix and establishing strong interfacial interactions remains the most challenging core scientific problem in this field.
[0003] Numerous explorations have been undertaken to improve the dispersibility of nanofillers. For example, Chinese patent CN112920415A (application number 202110028992.9, publication date June 8, 2021) discloses an amidated graphene / nylon 6 nanocomposite material and its preparation method. This method involves first activating the carboxyl groups of graphene oxide with a catalyst and then reacting it with an amino modifier to obtain amidated graphene powder. The powder is then added to a caprolactam melt and ultrasonically dispersed to form a dispersion. The dispersion is then polymerized under high temperature and pressure to obtain the nanocomposite material. Although this patent improves the compatibility between graphene and the nylon matrix through chemical modification, the amidation modification only introduces a single functional group, resulting in limited improvement in the dispersion of the nanofiller. Furthermore, ultrasonic dispersion in the polymer melt cannot ensure that the nanofiller achieves truly uniform nanoscale dispersion within the matrix.
[0004] Chinese patent CN107663276A (application number CN201610615951.9, publication date February 6, 2018) discloses a nanoparticle / polymer composite electret film and its preparation method. This method involves dispersing nanoparticles in a polymer solution, followed by film formation and heat treatment steps to obtain the composite film. However, this method only employs simple physical mixing, leading to easy agglomeration of nanoparticles in the polymer matrix, making it difficult to ensure uniform dispersion. Furthermore, the lack of effective interfacial bonding between the nanoparticles and the polymer matrix results in insufficient mechanical properties and long-term stability of the composite material.
[0005] Chinese patent CN112920538A (application number 2021101119234, publication date June 8, 2021) discloses a superelastic 3D printing nanocellulose composite material and its preparation method, which uses hollow porous nanocellulose and elastomer particles to achieve physical bonding. However, this method relies on the unique hollow porous structure of nanocellulose to achieve physical interlocking, which is not applicable to conventional nano-inorganic oxide fillers. Furthermore, the interfacial bonding strength of physical bonding is limited, and interfacial debonding is prone to occur during long-term use.
[0006] Chinese patent CN115651610A (application number CN202211178225.7, published on January 31, 2023) discloses a shaped composite phase change material based on a novel nano-ceramic framework. The resulting composite material has a high thermal decomposition temperature. However, this patent mainly focuses on the field of phase change thermal storage and does not solve the problem of dispersion of nanofillers in non-polar or weakly polar polymer matrices.
[0007] Therefore, existing technologies still have significant shortcomings in the surface functionalization design of nanofillers, the regulation of interfacial interactions, and the control of nanoscale dispersion stability. Specifically, existing surface modification methods typically only perform single chemical modifications on nanofillers, resulting in limited modification layer thickness and density, making it difficult to form a sufficiently strong steric hindrance effect in the polymer matrix. Conventional physical blending methods struggle to achieve uniform dispersion of nanofillers in the polymer matrix, and the presence of numerous agglomerates severely restricts the performance of nanocomposites. Furthermore, existing methods generally lack precise design of the interfacial chemical structure, leading to insufficient interfacial bonding strength between the nanofillers and the polymer matrix, making the composite material prone to interfacial debonding and stress concentration under stress.
[0008] Therefore, developing a nanopolymer material and its preparation method that can effectively solve the problem of nanofiller dispersion, achieve strong interfacial bonding between nanofillers and polymer matrix, and possess excellent mechanical properties, thermal stability and low dielectric properties has significant technical value and broad application prospects. Summary of the Invention
[0009] The purpose of this invention is to provide a nano-polymer material and its preparation method. Specifically, the technical problems to be solved by this invention include: (1) the problem that nano-inorganic oxide particles are easy to agglomerate in polymer matrix and it is difficult to achieve uniform dispersion at the nanoscale; (2) the problem that existing surface modification methods only modify nanofillers and the interfacial bonding strength is insufficient; (3) the problem that existing nanocomposite materials are difficult to take into account excellent mechanical properties, high thermal stability and low dielectric properties.
[0010] To address the aforementioned technical problems, this invention proposes a nanopolymer material and its preparation method.
[0011] A first aspect of the present invention provides a nanopolymer material comprising a polymer matrix and surface-modified nanofillers dispersed in the polymer matrix.
[0012] In the technical solution of this invention, the surface-modified nanofiller is obtained through the following multi-step modification process: First, the nano-inorganic oxide particles are chemically grafted and modified with a silane coupling agent containing double bonds to form a pre-modified nanofiller; then, the pre-modified nanofiller and reactive monomers are grafted together in situ with a free radical polymerization under the action of an initiator to form a polymer brush layer on the surface of the nanofiller, thereby obtaining the surface-modified nanofiller.
[0013] This invention achieves precise control over the surface chemical structure and microstructure of nanofillers through a multi-step modification process. Specifically, the first stage, silane coupling agent modification, introduces double-bonded functional groups capable of participating in free radical polymerization onto the nanofiller surface, forming an organic modification layer with an appropriate grafting density. The second stage, in-situ free radical polymerization grafting, constructs a polymer brush layer with specific chemical composition, molecular weight, and chain length on the nanofiller surface. This polymer brush layer, on the one hand, shares the same chemical structure and good compatibility with the subsequent composite polymer matrix; on the other hand, it effectively inhibits the aggregation of nanofillers through the steric hindrance effect of the polymer brush chains. A significant synergistic effect exists between the two stages of modification: the introduction of the silane coupling agent provides ample active grafting sites for the second-stage polymerization, while the introduction of the polymer brush in the second stage further enhances steric hindrance and interfacial compatibility. The combination of these two processes enables the dispersion stability of the nanofillers in the polymer matrix to reach a level that conventional single modification methods cannot achieve.
[0014] Furthermore, the nano-inorganic oxide particles are preferably selected from nano-silica, nano-titanium dioxide, nano-alumina, or combinations thereof, and the average particle size of the nano-inorganic oxide particles is 10–80 nm.
[0015] Furthermore, the silane coupling agent containing double bonds is preferably selected from γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, or combinations thereof, and the amount of silane coupling agent used is 5-30% of the mass of the nano-inorganic oxide particles. γ-methacryloxypropyltrimethoxysilane (KH570) is a particularly preferred coupling agent, as the acryloxy group in its molecular structure has high free radical polymerization activity and can provide abundant reaction sites for the second-stage graft polymerization.
[0016] Furthermore, the reactive monomer is preferably selected from methyl methacrylate, butyl acrylate, styrene, acrylonitrile or a combination thereof, and the amount of reactive monomer used in the in-situ free radical polymerization grafting is 20 to 150% of the mass of the pre-modified nanofiller.
[0017] Furthermore, the polymer matrix is selected from thermoplastic polymers, thermosetting polymers, or combinations thereof, and is preferably selected from polymethyl methacrylate, polystyrene, polycarbonate, polypropylene, epoxy resin, or combinations thereof.
[0018] Furthermore, the content of surface-modified nanofillers in the polymer matrix is 0.5–10 wt%, and the surface-modified nanofillers are uniformly dispersed at the nanoscale in the polymer matrix, with the maximum size of their aggregates not exceeding 150 nm.
[0019] A second aspect of the present invention provides a method for preparing the above-mentioned nanopolymer material, comprising the following steps: (a) Disperse nano-inorganic oxide particles in an organic solvent, add a silane coupling agent containing double bonds for chemical grafting modification, the reaction temperature is 50-120℃, the reaction time is 4-24 hours, and after separation, washing and drying, the pre-modified nanofiller is obtained. (b) The pre-modified nanofiller obtained in step (a) is dispersed in reactive monomers, and an initiator is added for in-situ free radical polymerization grafting. The reaction temperature is 60-100℃ and the reaction time is 6-48 hours. After separation, washing and drying, the surface-modified nanofiller is obtained. (c) The surface-modified nanofiller obtained in step (b) is compounded with a polymer matrix or its precursor in a solvent or in a molten state, and after uniform mixing, it is cured or shaped to obtain a nano-polymer material.
[0020] The preparation method of this invention is characterized by its simplicity, mild process conditions, and ease of large-scale production. The key process parameters for each step can be flexibly adjusted within the aforementioned range to achieve optimal compatibility with different types of polymer matrices and nanofillers.
[0021] Preferably, the organic solvent in step (a) is selected from toluene, xylene, tetrahydrofuran, acetone or a combination thereof, and the chemical grafting modification is carried out under nitrogen protection.
[0022] Preferably, in step (b), the initiator is selected from azobisisobutyronitrile, benzoyl peroxide or a combination thereof, and the amount of initiator is 0.5 to 5% of the mass of the reactive monomer.
[0023] Preferably, the composite method in step (c) is selected from solution blending, melt blending, in-situ polymerization, or a combination thereof. Specifically, when in-situ polymerization is used, the surface-modified nanofiller is uniformly dispersed in the polymer monomer, an initiator is added to initiate the polymerization reaction, the polymerization temperature is 60–150°C, and the polymerization time is 4–48 hours. After polymerization, the nanopolymer material is obtained through degassing, casting, and curing. In-situ polymerization enables the simultaneous generation and in-situ composite of the nanofiller with the polymer matrix during polymerization, which helps to obtain optimal dispersion and interfacial bonding strength.
[0024] As an improvement, the beneficial effects of the present invention are as follows: (1) This invention constructs a polymer brush layer with specific chemical composition and chain length on the surface of nanofillers through a multi-step surface modification strategy of "silane coupling agent chemical grafting + in-situ free radical polymerization grafting". The polymer brush layer has good chemical compatibility with the polymer matrix and can effectively inhibit the aggregation of nanofillers through steric hindrance effect, so that the nanofillers can achieve true nanoscale uniform dispersion in the polymer matrix.
[0025] (2) In the surface-modified nanofiller prepared by the present invention, the polymer brush layer is firmly connected to the surface of the nanofiller through chemical bonds (Si-O-Si bonds formed by silane coupling agent and CC bonds formed by free radical polymerization), forming a strong interfacial bond with the polymer matrix. It can effectively transfer load during the stress process of the composite material and significantly improve the mechanical properties of the composite material.
[0026] (3) The nanopolymer material obtained by the present invention has excellent mechanical properties, thermal stability and low dielectric properties, and can be widely used in the fields of electronic information, aerospace, new energy and other high-tech fields to meet the urgent needs of high-performance structural materials and functional materials.
[0027] (4) The preparation method of the present invention has mild process conditions, simple operation, and no special equipment required. It is suitable for large-scale industrial production and has significant economic benefits and industrial application value. Detailed Implementation
[0028] The specific embodiments of the present invention are further described below. Identical components are indicated by the same reference numerals. It should be noted that the terms "front," "rear," "left," "right," "up," and "down" used in the following description refer to directions in the center, while the terms "inner" and "outer" refer to directions toward or away from the geometric center of a specific component.
[0029] To make the content of this invention easier to understand, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Identical components are represented by the same reference numerals.
[0030] In the following examples, all raw materials and reagents used were commercially available products with analytical or industrial purity grades, and their specific sources are as follows: Nano-silica: average particle size 20nm, purity 99wt%, purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd., specific surface area approximately 140m². 2 / g.
[0031] Nano titanium dioxide: average particle size 30nm, purity 99.5%, purchased from Hangzhou Wanjing New Materials Co., Ltd.
[0032] Nano-alumina: average particle size 40nm, purity 99.9%, purchased from Shanghai Chaowei Nanotechnology Co., Ltd.
[0033] γ-Methacryloxypropyltrimethoxysilane (KH570): 98% purity, purchased from Nanjing Shuguang Chemical Group Co., Ltd.
[0034] Methyl methacrylate (MMA): 99% purity, purchased from Sinopharm Chemical Reagent Co., Ltd., and the polymerization inhibitor was removed by vacuum distillation before use.
[0035] Azobisisobutyronitrile (AIBN): 99% purity, purchased from Aladdin Reagent (Shanghai) Co., Ltd., and purified by recrystallization with anhydrous ethanol before use.
[0036] Polymethyl methacrylate (PMMA): molecular weight Mw≈120,000, purchased from Evonik Industrial Group, Germany.
[0037] Epoxy resin (E-51 type): epoxy value 0.51eq / 100g, purchased from Baling Petrochemical Company.
[0038] 4,4'-Diaminodiphenylmethane (DDM): 99% purity, purchased from Shanghai Maclean Biochemical Technology Co., Ltd.
[0039] Initiator benzoyl peroxide (BPO): 98% purity, purchased from Sinopharm Chemical Reagent Co., Ltd.
[0040] The specific embodiments of the present invention first describe in detail the preparation methods of pre-modified nanofillers and surface-modified nanofillers. Then, using polymethyl methacrylate and epoxy resin as typical polymer matrices, several specific preparation examples and comparative examples are given respectively. The prepared nanopolymer materials are subjected to comprehensive performance tests and characterization to fully support and verify the technical solutions defined in the claims.
[0041] I. Preparation of Pre-Modified Nanofillers Preparation Example 1 (Pre-modified nano-silica-KH570) 10.0 g of nano-silica (average particle size 20 nm) was dispersed in 200 mL of anhydrous toluene and ultrasonically dispersed for 30 minutes (ultrasonic power 300 W, frequency 40 kHz). The dispersion was then transferred to a 500 mL three-necked flask equipped with a mechanical stirrer and a reflux condenser. Under nitrogen protection, 2.0 g of KH570 (20% of the mass of nano-silica) was slowly added and stirred until homogeneous. The reaction system was heated to 110 °C and refluxed under constant temperature for 12 hours. During the reaction, the characteristic peak of Si-OH (approximately 3440 cm⁻¹) was monitored by infrared spectroscopy. -1 ) and Si-O-Si characteristic peak (approximately 1100 cm⁻¹) -1 The changes in [the product's composition] were monitored to track the reaction progress. After the reaction was complete, the product was cooled to room temperature and the solid product was separated by high-speed centrifugation (12000 rpm, 15 minutes). The product was washed three times with anhydrous ethanol to remove unreacted silane coupling agent and byproducts, and then dried in a vacuum drying oven at 60°C for 12 hours to obtain pre-modified nano-silica-KH570. Thermogravimetric analysis showed that the grafting rate of KH570 on the surface of nano-silica was approximately 9.5%.
[0042] Preparation Example 2 (Pre-modified nano-titanium dioxide-vinyltriethoxysilane) 10.0 g of nano-titanium dioxide (average particle size 30 nm) was dispersed in 200 mL of tetrahydrofuran and ultrasonically dispersed for 30 minutes before being transferred to a 500 mL three-necked flask. Under nitrogen protection, 1.5 g of vinyltriethoxysilane (15% of the mass of nano-titanium dioxide) was added, and the mixture was heated to 65 °C and reacted for 8 hours. After the reaction was completed, the mixture was centrifuged, washed three times with tetrahydrofuran, and dried under vacuum at 60 °C for 12 hours to obtain pre-modified nano-titanium dioxide-vinyltriethoxysilane.
[0043] Preparation Example 3 (Pre-modified nano-alumina-vinyltrimethoxysilane) 10.0 g of nano-alumina (average particle size 40 nm) was dispersed in 200 mL of xylene and ultrasonically dispersed for 30 minutes before being transferred to a 500 mL three-necked flask. Under nitrogen protection, 1.0 g of vinyltrimethoxysilane (10% of the mass of nano-alumina) was added, and the mixture was heated to 120 °C and reacted for 10 hours. After the reaction was completed, the mixture was centrifuged, washed three times with xylene, and dried under vacuum at 60 °C for 12 hours to obtain pre-modified nano-alumina-vinyltrimethoxysilane.
[0044] Comparative preparation example 4 (unmodified nano-silica) Raw nano-silica (average particle size 20 nm) was used directly as a control.
[0045] II. Preparation of Surface-Modified Nanofillers Preparation Example 5 (Surface-Modified Nano-Silica-PMMA Brush) 5.0 g of the pre-modified nano-silica-KH570 obtained in Preparation Example 1 was dispersed in 100 mL of methyl methacrylate (MMA) monomer and ultrasonically dispersed for 30 minutes to form a stable dispersion. The dispersion was transferred to a 250 mL three-necked flask, heated to 75 °C under nitrogen protection, and 0.15 g of initiator AIBN (3% of the MMA mass) was added. In-situ free radical polymerization grafting reaction was carried out under constant temperature and stirring conditions for 24 hours. During the reaction, the monomer conversion rate was measured periodically to control the reaction progress. After the reaction, the product was centrifuged, repeatedly washed with toluene to remove unreacted monomers and free polymers, washed with ethanol, and finally dried in a vacuum drying oven at 60 °C to constant weight to obtain a surface-modified nano-silica-PMMA brush. Thermogravimetric analysis showed that the surface polymer grafting rate was approximately 45% (based on the mass of the pre-modified nanofiller).
[0046] Preparation Example 6 (Surface-Modified Nano-Titanium Dioxide-PMMA Brush) 5.0 g of the pre-modified nano-titanium dioxide-vinyltriethoxysilane obtained in Preparation Example 2 was dispersed in a mixture of 80 mL MMA and 20 mL butyl acrylate monomers and ultrasonically dispersed for 30 minutes. Under nitrogen protection, the temperature was raised to 80 °C, and 0.12 g AIBN (1.2% of the mixed monomer mass) was added, and the reaction was carried out for 20 hours. After centrifugation, washing with toluene and ethanol, and vacuum drying at 60 °C, surface-modified nano-titanium dioxide-(PMMA-co-PBA) brushes were obtained.
[0047] Preparation Example 7 (Surface-Modified Nano-Alumina-Polystyrene Brush) 5.0 g of the pre-modified nano-alumina-vinyltrimethoxysilane obtained in Preparation Example 3 was dispersed in 100 mL of styrene monomer and ultrasonically dispersed for 30 minutes. Under nitrogen protection, the temperature was raised to 85 °C, and 0.10 g of BPO (2% of the styrene mass) was added, and the reaction was carried out for 24 hours. After centrifugation, washing with toluene and ethanol, and vacuum drying at 60 °C, the surface-modified nano-alumina-polystyrene brush was obtained.
[0048] Comparative preparation example 8 (KH570 modified nano-silica only) Only the first step of the modification in Preparation Example 1 was performed, that is, only KH570 was used to chemically graft the nano-silica, without performing the second stage of in-situ polymerization grafting, to obtain nano-silica modified only by KH570.
[0049] III. Preparation and Performance Testing of Nanopolymer Materials Example 1 (Solution blending method—PMMA / modified nano silica composite material) This embodiment provides a specific implementation method for preparing PMMA / surface-modified nano-silica composite materials using a solution blending method.
[0050] First, a surface-modified nano-silica-PMMA brush was prepared according to the method in Preparation Example 5. Then, 2.5 g of this surface-modified nano-silica-PMMA brush (equivalent to approximately 2.5 wt% of the surface-modified nanofiller content in the final composite material) was dispersed in 200 mL of tetrahydrofuran and ultrasonically dispersed for 60 minutes (ultrasonic power 400 W, frequency 40 kHz) to obtain a stable nanofiller dispersion. Separately, 97.5 g of PMMA (molecular weight Mw ≈ 120,000) was dissolved in 300 mL of tetrahydrofuran and stirred until completely dissolved. The nanofiller dispersion was slowly added dropwise to the PMMA solution, and stirring was continued at room temperature for 6 hours to ensure thorough mixing. The mixture was poured into a polytetrafluoroethylene mold and allowed to stand at room temperature for 12 hours to allow the solvent to slowly evaporate. Then, it was transferred to a vacuum oven and dried at 60°C for 48 hours to completely remove residual solvent. The dried film was hot-pressed at 180°C (pressure 10 MPa, holding pressure for 5 minutes), and after cooling, a PMMA / surface-modified nano-silica composite material was obtained, which was designated as the sample of Example 1.
[0051] Example 2 (In-situ polymerization method—PMMA / modified nano silica composite material) This embodiment provides a specific implementation method for preparing PMMA / surface-modified nano-silica composite materials using in-situ polymerization.
[0052] First, surface-modified nano-silica-PMMA brushes were prepared according to the method in Preparation Example 5. 100g of MMA monomer was added to a 500mL three-necked flask, followed by 2.5g of surface-modified nano-silica-PMMA brushes (equivalent to approximately 2.5wt% of the surface-modified nanofiller content in the final composite material). The mixture was ultrasonically dispersed for 60 minutes to form a uniform dispersion. Under nitrogen protection, the temperature was raised to 75°C, and 0.5g of initiator AIBN (0.5% of the MMA mass) was added. Polymerization was carried out under constant temperature stirring. During the reaction, the temperature was controlled by an oil bath, maintaining the reaction temperature at 75±2°C. After 10 hours of continuous polymerization, the viscosity of the system increased significantly, and the polymerization conversion rate was measured to be over 92%. The polymerized product was degassed in an 80°C vacuum oven for 2 hours to remove bubbles and residual monomers. It was then poured into a preheated glass mold and post-cured at 110°C for 4 hours to ensure complete polymerization. After cooling, the product was demolded to obtain the PMMA / surface-modified nano-silica composite material, designated as Sample 2.
[0053] Example 3 (Mel Blending Method—PMMA / Modified Nano-Silica Composite Material) This embodiment provides a specific implementation method for preparing PMMA / surface-modified nano-silica composite materials using a melt blending method.
[0054] First, surface-modified nano-silica-PMMA brushes were prepared according to the method in Example 5. 97.5g of PMMA granules and 2.5g of surface-modified nano-silica-PMMA brushes were premixed in a high-speed mixer for 5 minutes (1500 rpm). The mixture was then melt-blended and extruded through a twin-screw extruder. The extruder temperatures were set as follows: feeding section 170°C, compression section 190°C, metering section 200°C, die head temperature 195°C, and screw speed 120 rpm. After water cooling, pelletizing, and drying, the extrudate was injection molded into standard test specimens (injection temperature 200°C, mold temperature 60°C, injection pressure 80 MPa) to obtain a PMMA / surface-modified nano-silica composite material, designated as Sample 3.
[0055] Example 4 (Changing the filler content) This embodiment investigates the effect of the content of surface-modified nanofillers on the properties of composite materials. PMMA composite materials with different contents of surface-modified nano-silica-PMMA brushes were prepared by in-situ polymerization as described in Example 2, with the surface-modified nanofiller contents set at 0.5 wt%, 1.5 wt%, 3.0 wt%, 5.0 wt%, and 8.0 wt%, respectively. The specific preparation method was the same as in Example 2, only the amount of surface-modified nanofiller added was adjusted. The prepared samples are designated as Examples 4-1 to 4-5, respectively.
[0056] Example 5 (Epoxy Resin-Based Composite Material) This embodiment provides a specific implementation method for preparing nanopolymer materials using epoxy resin as the polymer matrix.
[0057] First, a surface-modified nano-silica-PMMA brush was prepared according to the method in Example 5. 100g of epoxy resin (E-51 type) and 3.0g of surface-modified nano-silica-PMMA brush (equivalent to approximately 3.0wt% of the surface-modified nanofiller content in the final composite material) were added to a 500mL three-necked flask. The mixture was mechanically stirred at 60°C for 2 hours to ensure uniform dispersion of the nanofiller, while simultaneously undergoing vacuum degassing. Then, 26.5g of curing agent DDM (calculated based on an epoxy group to amino hydrogen equivalent ratio of 1:1) was added, and stirring continued for 15 minutes to ensure complete dissolution and uniform dispersion of the curing agent. The mixture was poured into a metal mold pre-coated with a release agent, pre-cured in a vacuum oven at 80°C for 2 hours, then heated to 150°C and cured for 4 hours. After natural cooling to room temperature, the mixture was demolded to obtain the epoxy resin / surface-modified nano-silica composite material, designated as Sample 5.
[0058] Comparative Example 1 (Pure PMMA) Using the same method as in Example 2, bulk polymerization of MMA monomers was carried out without the addition of any nanofillers to prepare a pure PMMA sample, denoted as Comparative Example 1.
[0059] Comparative Example 2 (PMMA / unmodified nano-silica composite material) The same in-situ polymerization method as in Example 2 was used, but unmodified nano-silica (comparative preparation example 4, average particle size 20 nm) was directly added instead of the surface-modified nano-silica-PMMA brush, and the nanofiller content was 2.5 wt% to prepare PMMA / unmodified nano-silica composite material, which is referred to as Comparative Example 2.
[0060] Comparative Example 3 (PMMA / KH570-modified nano-silica composite material) Using the same in-situ polymerization method as in Example 2, but adding only KH570 modified nano-silica (Comparative Preparation Example 8) instead of the surface-modified nano-silica-PMMA brush, with a nanofiller content of 2.5 wt%, PMMA / KH570 modified nano-silica composite material was prepared, denoted as Comparative Example 3.
[0061] Comparative Example 4 (pure epoxy resin) Using the same method as in Example 5, but without adding any nanofillers, a pure epoxy resin sample was prepared and designated as Comparative Example 4.
[0062] IV. Performance Testing and Characterization The samples prepared in the above embodiments and comparative examples were subjected to systematic performance testing and characterization. The specific test methods and results are as follows.
[0063] 4.1 Test Method (1) Dispersion morphology characterization: The dispersion morphology of the nanofillers in the polymer matrix was observed using transmission electron microscopy (TEM, JEOL JEM-2100F, accelerating voltage 200kV). The samples were prepared by low-temperature sectioning at -120℃ using an ultramicrotome (Leica UC7), with a section thickness of approximately 70nm. The aggregate size in at least 50 fields of view was statistically analyzed using ImageJ image analysis software, and the average value was taken as the maximum aggregate size.
[0064] (2) Tensile property test: The test was conducted using a universal testing machine (Instron 5967) in accordance with GB / T 1040.2-2006 standard. Test conditions: temperature 23±2℃, relative humidity 50±5%, tensile rate 5mm / min. At least 5 parallel samples were tested for each type of sample, and the average value and standard deviation of the results were taken.
[0065] (3) Thermal decomposition temperature test: Thermogravimetric analysis (TGA, TA Instruments Q500) was used for the test under a nitrogen atmosphere. Test conditions: heating rate 10℃ / min, temperature range 30~800℃, nitrogen flow rate 60mL / min. The temperature corresponding to 5% thermal weight loss (T5%) was recorded as the characterization parameter of thermal decomposition temperature, and the temperature corresponding to the maximum thermal weight loss rate (Tmax) was also recorded.
[0066] (4) Dielectric constant test: The test was conducted at room temperature using a precision impedance analyzer (Agilent 4294A). The test frequency range was 1 kHz to 1 MHz. Before the test, gold electrodes (approximately 10 mm in diameter) were deposited on both sides of the sample, and the sample thickness was controlled between 0.5 and 1.0 mm. The dielectric constant at 1 MHz was recorded.
[0067] 4.2 Test Results 4.2.1 Results of Dispersion Morphology Characterization TEM observations showed that in the PMMA / surface-modified nano-silica composite material prepared in Example 2, the nanofiller exhibited a highly uniform monodisperse state, with the largest agglomerate size being approximately 80–120 nm. The vast majority of nanoparticles were uniformly distributed as individual particles within the PMMA matrix, and no obvious agglomerates were observed. The interface between the nanofiller and the PMMA matrix was blurred, indicating good compatibility between the polymer brush and the matrix.
[0068] In contrast, in Comparative Example 2 (PMMA / unmodified nano-silica), severe agglomeration of nano-silica was observed, with agglomerate sizes exceeding 500 nm. In some areas, even large micron-sized agglomerates (2–5 μm) appeared, indicating extremely uneven distribution of the nanofiller within the matrix. In Comparative Example 3 (PMMA / KH570-modified nano-silica only), the dispersion of the nanofiller was somewhat improved, but the agglomerate size still reached 200–350 nm, and the distribution was not uniform, with significant filler aggregation still present in some areas.
[0069] The above results demonstrate that the multi-step surface modification strategy proposed in this invention can effectively suppress the aggregation of nanofillers in the polymer matrix and achieve true nanoscale uniform dispersion.
[0070] 4.2.2 Tensile property test results The tensile property test results of each embodiment and comparative example are summarized in Table 1.
[0071] Table 1 Tensile properties of samples from each embodiment and comparative example
[0072] As shown in Table 1, the tensile strength of Example 2 (in-situ polymerization, 2.5 wt% surface-modified nanofiller) reached 78.6 MPa, which was 26.2% higher than that of Comparative Example 1 (pure PMMA, 62.3 MPa). Simultaneously, the tensile modulus increased from 2.85 gPa to 3.45 gPa (an increase of 21.1%), and the elongation at break also increased from 4.2% to 5.2%. It is noteworthy that the tensile strength of Comparative Example 2 (direct addition of unmodified nano-silica) was actually lower than that of pure PMMA. This is attributed to stress concentration and interfacial debonding caused by severe agglomeration and poor interfacial bonding of the unmodified nanofiller. The tensile strength of Comparative Example 3 (KH570 modification only) was 68.5 MPa, which, although improved compared to pure PMMA, was still significantly lower than that of Example 2. This fully demonstrates that the introduction of the polymer brush layer in the multi-step modification strategy of this invention has a far greater enhancing effect on mechanical properties than modification with a single silane coupling agent. For the epoxy resin system, the tensile strength (89.3 MPa) of Example 5 was 30.0% higher than that of the pure epoxy resin in Comparative Example 4 (68.7 MPa), and the tensile modulus was 29.5% higher, further verifying the universality of the technical solution of the present invention in different polymer matrix systems.
[0073] The tensile property test results of samples with different filler contents in Example 4 show that as the content of surface modified nanofiller increases from 0.5 wt% to 3.0 wt%, the tensile strength and tensile modulus of the composite material gradually increase; when the filler content exceeds 5.0 wt%, the increase in mechanical properties gradually slows down, indicating that better comprehensive mechanical properties can be achieved in the filler content range of 3 to 5 wt%.
[0074] 4.2.3 Thermal decomposition temperature test results The TGA test results are shown in Table 2.
[0075] Table 2. Thermal decomposition temperatures of each embodiment and comparative sample.
[0076] As shown in Table 2, the thermal decomposition temperature (T5%) of Example 2 was 336.7℃, which was 24.2℃ higher than that of pure PMMA in Comparative Example 1 (312.5℃) and 12.4℃ higher than that of Comparative Example 3 (324.3℃). The thermal decomposition temperature (T5%) of Example 5 was 351.2℃, which was 22.6℃ higher than that of pure epoxy resin in Comparative Example 4 (328.6℃). The improvement in thermal stability is mainly attributed to the following factors: the uniformly dispersed nanofillers formed a physical network structure in the polymer matrix, which restricted the thermal movement of polymer chain segments; the chemical compatibility and strong interfacial bonding between the polymer brushes on the surface of the nanofillers and the matrix effectively hindered the diffusion and volatilization of low molecular weight compounds during thermal decomposition; and the nanofillers themselves have high thermal stability and thermal barrier effect.
[0077] 4.2.4 Dielectric constant test results The dielectric constant test results at 1 MHz are shown in Table 3.
[0078] Table 3. Dielectric constants (1MHz) of each embodiment and comparative sample.
[0079] As shown in Table 3, the dielectric constant of Example 2 is 2.7, significantly lower than that of pure PMMA (3.2) and also lower than that of Comparative Example 3 (3.1). The decrease in dielectric constant is attributed to the introduction of the surface polymer brush layer, which forms a low-polarity interface layer between the nanofiller and the matrix. Simultaneously, the uniform dispersion of the nanofiller prevents localized enrichment of high-dielectric-constant fillers. The dielectric constant of Example 5 decreased from 3.9 (pure epoxy resin) to 3.0, a reduction of 23.1%, further demonstrating the application potential of this invention in the field of low-dielectric materials.
[0080] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A graphene-modified polymer material, characterized in that, The graphene is prepared by the following method: dispersing graphene in a first organic solvent, adding a surface modifier to perform surface functionalization modification, and obtaining surface-functionalized graphene; mixing the surface-functionalized graphene with a polymer monomer, and grafting polymer chains onto the graphene surface through in-situ polymerization to obtain polymer-grafted modified graphene; blending the polymer-grafted modified graphene with a polymer matrix resin and granulating to obtain a graphene-modified polymer material; wherein the surface modifier is an aromatic compound or heterocyclic compound containing at least one carboxyl, hydroxyl, or amino group, and the polymer monomer is selected from at least one of lactams, combinations of diacids and diamines, cyclic esters, or cyclic ethers.
2. The graphene-modified polymer material according to claim 1, characterized in that, The surface modifier is selected from at least one of p-aminobenzoic acid, m-aminobenzoic acid, o-aminobenzoic acid, 4-aminosalicylic acid, 2-aminoterephthalic acid, 3,5-diaminobenzoic acid, 2-mercaptobenzothiazole, 2-mercaptobenzimidazole, 2-mercaptobenzoxazole, nicotinic acid, isonicotinic acid, and 2-pyridinecarboxylic acid.
3. The graphene-modified polymer material according to claim 1, characterized in that, The mass ratio of graphene to surface modifier is 1:0.5 to 1:5, the reaction temperature for surface functionalization modification is 60 to 120°C, and the reaction time is 4 to 12 hours.
4. The graphene-modified polymer material according to claim 1, characterized in that, The in-situ polymerization reaction is as follows: surface-functionalized graphene is mixed with caprolactam monomer at a mass ratio of 1:50 to 1:500, heated to 220 to 280°C under inert gas protection, and an initiator is added to carry out a ring-opening polymerization reaction for 4 to 10 hours to obtain polyamide 6 grafted modified graphene.
5. The graphene-modified polymer material according to claim 1, characterized in that, The in-situ polymerization reaction is as follows: surface-functionalized graphene is mixed with lactide monomer at a mass ratio of 1:30 to 1:300, heated to 130 to 180°C under inert gas protection, and ring-opening polymerization is carried out by adding stannous octoate catalyst for 6 to 24 hours to obtain polylactic acid grafted modified graphene.
6. The graphene-modified polymer material according to claim 1, characterized in that, The polymer matrix resin is selected from at least one of polyamide 6, polyamide 66, polylactic acid, polyethylene terephthalate, polycarbonate, polypropylene, polyethylene, polystyrene, and polyvinyl chloride.
7. The graphene-modified polymer material according to claim 1, characterized in that, The mass ratio of the polymer grafted modified graphene to the polymer matrix resin is 1:99 to 1:
9.
8. A method for preparing a graphene-modified polymer material, characterized in that, Includes the following steps: (1) Surface functionalization modification: Graphene is ultrasonically dispersed in a first organic solvent, a surface modifier is added, and the reaction is stirred at 60-120℃ for 4-12 hours. After the reaction is completed, the graphene is centrifuged, washed with a second organic solvent, and vacuum dried to obtain surface functionalized graphene. (2) In-situ grafting polymerization: Surface functionalized graphene is mixed with polymer monomers, heated to the polymerization temperature of the monomers under inert gas protection, an initiator or catalyst is added, and the reaction is stirred for 4 to 24 hours. After the reaction is completed, the mixture is cooled and pulverized to obtain polymer grafted graphene. (3) Blending and granulation: The polymer grafted modified graphene obtained in step (2) is mixed with the polymer matrix resin in a certain proportion, and processing aids are added. The mixture is melt-blended and extruded and granulated by a twin-screw extruder to obtain graphene modified polymer material.
9. A method for preparing a graphene-modified polymer material according to claim 8, characterized in that, In step (3), the screw speed of the twin-screw extruder is 100-400 rpm, and the temperature of each zone is set as follows: Zone 1 160-200℃, Zone 2 180-240℃, Zone 3 200-260℃, Zone 4 200-260℃, Zone 5 190-250℃, and the die head temperature is 190-250℃.
Citation Information
Patent Citations
Nano particle-high molecular polymer composite electret thin film, preparation method thereof and triboelectric nano generator including thin film
CN107663276A
A nanoparticle-polymer composite electret thin film, its preparation method, and a triboelectric nanogenerator containing the thin film.
CN107663276B
Amidated graphene / nylon 6 nano composite material and preparation method thereof
CN112920415A
Hyper-elastic 3D printing nano cellulose composite material and preparation method thereof
CN112920538A
Sizing composite phase change material based on novel nano ceramic skeleton and preparation method of sizing composite phase change material
CN115651610A